2009
DOI: 10.1212/wnl.0b013e3181ab2b27
|View full text |Cite
|
Sign up to set email alerts
|

Very Early Constraint-Induced Movement during Stroke Rehabilitation (VECTORS)

Abstract: Constraint-induced movement therapy (CIMT) was equally as effective but not superior to an equal dose of traditional therapy during inpatient stroke rehabilitation. Higher intensity CIMT resulted in less motor improvement at 90 days, indicating an inverse dose-response relationship. Motor intervention trials should control for dose, and higher doses of motor training cannot be assumed to be more beneficial, particularly early after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
329
4
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(358 citation statements)
references
References 31 publications
13
329
4
12
Order By: Relevance
“…In a study on CIMT 9.65 ± 4.50 days after stroke, Dromerick et al assessed a subset of the subjects receiving control therapy, low-intensity CIMT, and high-intensity CIMT with magnetic resonance imaging techniques sensitive to changes following cerebral infarction. Although the sample size was small, no evidence was found for enlargement of the stroke lesion that could have explained the inverse dose-response observed [37].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In a study on CIMT 9.65 ± 4.50 days after stroke, Dromerick et al assessed a subset of the subjects receiving control therapy, low-intensity CIMT, and high-intensity CIMT with magnetic resonance imaging techniques sensitive to changes following cerebral infarction. Although the sample size was small, no evidence was found for enlargement of the stroke lesion that could have explained the inverse dose-response observed [37].…”
Section: Discussionmentioning
confidence: 80%
“…The latter result raises the possibility of a limit on the amount of RA training that is beneficial. Expansion of neural injury and reduced restoration of function associated with early forced use of a forelimb after unilateral brain injury has been seen in rats [37][38][39][40]. Although the applicability of these results to human trials has not been demonstrated, they point out the need to consider intensity, total dose, and timing of training in trials of novel therapeutic methods and devices.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, stroke induces the expression of specific pro-plastic genes defining an optimal time period in which training should be most effective (Carmichael et al 2005). In humans, using high-intensity constraint induced movement therapy (CIMT, 3 hours of training based on shaping principles plus immobilizing the intact limb for 90% of the waking hours for 10 days) starting around 10 days after stroke results in adverse outcomes as compared with standard occupational therapy and standard CIMT (two hours of shaping plus 6 hours of immobilization per day Dromerick et al 2009). In contrast, Bernhardt and coworkers suggested that early -within 24 hours -mobilization, i.e., getting the patient out of bed, improves the outcome three months after the stroke (Bernhardt et al 2008).…”
Section: Therapeutic Principles Timingmentioning
confidence: 99%
“…Whether training can be effectively enhanced by plasticity-encouraging interventions such as brain stimulation or certain drugs, remains to be proven by clinical research. What is known from experience as well as science is that higher intensity is more effective than lower intensity (Kwakkel et al 2004,Teasell et al 2005, although this may not hold true for early time points after injury (in this case, stroke, Dromerick et al 2009). High intensity training requires excellent patient compliance and motivation, the major limiting factors for successful training.…”
Section: Introductionmentioning
confidence: 99%
“…the outcome of disability secondary to stroke. [11][12][13][14] However, Dromericket al 15 concluded that increased dose of constraint-induced movement therapy may worsen the functional outcomes.It is also essential to point-out that the duration of physiotherapy that is typically provided to stroke patients is quite little. The common practice in the UK and most countries in Europe, are a paltry 20 to 30 minutes of physical therapy per day.…”
Section: Introductionmentioning
confidence: 99%